Amivantamab plus lazertinib in previously untreated EGFR-mutated advanced NSCLC - Cho, Byoung C.; Lu, Shun; Felip, Enriqueta; Spira, Alexander I.; Girard, Nicolas; Lee, Jong-Seok; Lee, Se-Hoon; Ostapenko, Yurii; Danchaivijitr, Pongwut; Liu, Baogang; Alip, Adlinda; Korbenfeld, Ernesto; et al. (The New England journal of medicine, 2024)
BACKGROUND: Amivantamab plus lazertinib (amivantamab-lazertinib) has shown clinically meaningful and durable antitumor activity in patients with previously untreated or osimertinib-pretreated EGFR (epidermal growth factor receptor)-mutated advanced non-small-cell lung cancer (NSCLC). - METHODS: In a phase 3, international, randomized trial, we assigned, in a 2:2:1 ratio, patients with previously untreated EGFR-mutated (exon 19 deletion or L858R), locally advanced or metastatic NSCLC to receive amivantamab-lazertinib (in an open-label fashion), osimertinib (in a blinded fashion), or lazertinib (in a blinded fashion, to assess the contribution of treatment components). The primary end point was progression-free survival in the amivantamab-lazertinib group as compared with the osimertinib group, as assessed by blinded independent central review. - RESULTS: Overall, 1074 patients underwent randomization (429 to amivantamab-lazertinib, 429 to osimertinib, and 216 to lazertinib). The median progression-free survival was significantly longer in the amivantamab-lazertinib group than in the osimertinib group (23.7 vs. 16.6 months; hazard ratio for disease progression or death, 0.70; 95% confidence interval [CI], 0.58 to 0.85; P<0.001). An objective response was observed in 86% of the patients (95% CI, 83 to 89) in the amivantamab-lazertinib group and in 85% of those (95% CI, 81 to 88) in the osimertinib group; among patients with a confirmed response (336 in the amivantamab-lazertinib group and 314 in the osimertinib group), the median response duration was 25.8 months (95% CI, 20.1 to could not be estimated) and 16.8 months (95% CI, 14.8 to 18.5), respectively. In a planned interim overall survival analysis of amivantamab-lazertinib as compared with osimertinib, the hazard ratio for death was 0.80 (95% CI, 0.61 to 1.05). Predominant adverse events were EGFR-related toxic effects. The incidence of discontinuation of all agents due to treatment-related adverse events was 10% with amivantamab-lazertinib and 3% with osimertinib. - CONCLUSIONS: Amivantamab-lazertinib showed superior efficacy to osimertinib as first-line treatment in EGFR-mutated advanced NSCLC. (Funded by Janssen Research and Development; MARIPOSA ClinicalTrials.gov number, NCT04487080.).